A multicentre study of coproxamol poisoning suicides based on coroners' records in England. - Hawton, K; Simkin, S; Gunnell, D; Sutton, L; Bennewith, O; Turnbull, P; Kapur, N (2005)
AIMS: To examine in detail a series of coproxamol overdose deaths in order to provide information that will assist in the development of strategies to prevent such fatalities. METHOD: Inquest records in 24 coroners' jurisdictions in England on deaths between January 2000 and December 2001 which received a verdict of either suicide or undetermined cause (with a high or moderate probability of suicide) were examined. RESULTS: One hundred and twenty-three coproxamol poisoning suicides were identified. Alcohol was involved in 58.5% of the overdoses and these individuals generally had lower blood drug levels and consumed fewer tablets. Younger people were more likely to have consumed alcohol and to have lower levels of suicide intent. Nearly half the individuals had a history of self harm, and a third were under psychiatric care. The coproxamol had been prescribed for the individual in 81.5% of cases, although only in 55.0% of those aged 10-34 years. In other cases the source of the coproxamol was nearly always a family member or partner. Some deaths resulted from relatively small overdoses. CONCLUSIONS: Strategies to reduce self poisoning deaths due to coproxamol should take account of the high toxicity of coproxamol in overdose, especially when combined with alcohol, and the fact that risk of death extends beyond the person for whom the drug is prescribed.